Implikasi Metode PBL Dalam Peningkatan Hasil Belajar Pendidikan Agama Katolik di SMP Negeri 1 Biatan - Yakobus Gala; Hartutik Hartutik (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This study addresses learning challenges, including student learning difficulties and the ineffective use of lecture-based methods, which result in boredom, disengagement, and low student participation. These issues contribute to poor learning outcomes and low completion rates. The aim of this study is to improve student independence and enhance both average scores and the percentage of learning completion by implementing the Problem Based Learning (PBL) model. This aligns with the principles of the flexible Independent Curriculum, which encourages teachers to adopt student-centered learning approaches that enhance outcomes. The study employed a descriptive-qualitative method, structured in two cycles consisting of planning, implementation, evaluation, and reflection. The research involved eight 8th-grade students at SMPN 1 Biatan during the 2024/2025 academic year. The study focused on developing the